Mal de Meleda with lip involvement: A report of two cases - Amiya Kumar Nath; Sangita Chaudhuri; Devinder Mohan Thappa (Wolters Kluwer Medknow Publications, 2012)
Mal de Meleda is a rare autosomal recessive transgradient palmoplantar keratoderma characterized by transgradient keratoderma with associated scleroatrophy, nail changes, pseudoainhum around digits and perioral erythema, without a tendency for spontaneous resolution. Involvement of the lip by keratoderma has not been reported in the English literature. Here we present two cases of Mal de Meleda with unusual lip involvement. The first case was a 15-year-old girl, born of second-degree consanguineous marriage, who presented with transgradient palmoplantar keratoderma from 6 months of age, with lichenoid papules and plaques on the elbows and knees, conical tapering of the distal digits, flexion deformity of several fingers, digital constriction, knuckle pads and lip involvement. The second case was a 24-year-old male with transgradient palmoplantar keratoderma since birth. He also had scaly plaques on the extensors of bilateral knees and elbows, knuckle pads, pseudosclerodermatous fingers with conical tapering, digital constrictions at various places with mild flexion deformity and lip involvement. Both patients were otherwise normal without any family history.